Power and paradise in Walt Disney's world - Knight, Cher Krause (University Press of Florida, 2014)
"From the four corners of the world, parents gather their children, pack their suitcases, and make the journey to Disney World in central Florida. Honeymooners choose the destination over countless others. Its symbols--whether the three overlapping circles that create a mouse's head or Cinderella's Castle with a shooting star over the turrets--are recognized around the globe. It has had nearly one billion visitors since opening in 1971. In this fascinating analysis, Cher Krause Knight peels back the actual and contextual layers of Walt Disney's inspiration and vision for the resort to explore the reasons why Disney World has emerged as such a prominent sociocultural force. Every detail, from the scale and design of the buildings to the sidewalk infrastructure to what items could and could not be sold in the shops, was carefully calculated to shape the experience of each visitor. Expertly weaving themes of pilgrimage, paradise, fantasy, and urbanism, Knight delves into the unexpected nuances and contradictions of this elaborately conceived playland of the imagination"--Provided by publisher